Fundamental Solutions to the Cosserat Type Model of Honeycomb Grid in a Plane-Stress State - Lewiński, T. (Engineering Transactions, 1984)
In the paper fundamental solutions to the continuum Woźniak’s type model of elastic grid disk of honcycomb structure are found; the singularities of displacements, strains, stresses as well as couple stresses are displayed and examined. In a particular case when constitutive equations are decoupled, the solutions obtained reduce to the well known components of the Green tensor for an isotropic and centrosymmetric Cosserat medium in a plane stress state.